A study of adsorption in aqueous solution of p,o,m-Chlorophenol on Iraqi siliceouns rocks powder - Ammar J. Mohammed (مجلة بغداد للعلوم, 2007)
Adsorption of Chlorophenol compounds in aqueous solution on Iraqi siliceouns rocks powder have been investigated. UV technique has been used to determine the adsorption isotherms. The results showed that the adsorption isotherms obeyed Freundlich adsorption equation.